Structure and topology of three‐dimensional hydrocarbon polymers. Issue 4 (3rd August 2016) - Kondrin, Mikhail V.; Lebed, Yulia B.; Brazhkin, Vadim V.
Abstract : A new family of three‐dimensional hydrocarbon polymers with no known structural analogs which are more energetically favorable than benzene is proposed. Abstract : A new family of three‐dimensional hydrocarbon polymers which are more energetically favorable than benzene is proposed. Although structurally these polymers are closely related to well known diamond and lonsdaleite carbon structures, using topological arguments we demonstrate that they have no known structural analogs. Topological considerations also give some indication of possible methods of synthesis. Taking into account their exceptional optical, structural and mechanical properties these polymers might have interesting applications.